IMMUNOLOGICAL MECHANISMS OF APOPTOSIS IN PLACENTAL DEVELOPMENT - D. I. Sokolov (Медицинская иммунология, 2014)
Abstract. In present review, the data are considered that concern a role of immunological mechanisms controlling the events of apoptosis at different stages of development of placenta. Intensity of apoptotic process in human placenta is progressively increasing in the course of pregnancy, until delivery act. The processes of apoptosis induction and its prevention in placental cells are inseparably linked to development of placenta and formation of vascular system, as controlled by trophoblast cells, as well as by maternal fetal immune cells. T-lymphocytes, natural killer cells, NKT-cells and macrophages that perform surveillance over the processes of angiogenesis and apoptosis in placental tissue, thus providing its normal development and functioning.